U.S. Foreign Policy and the Law of the Sea - Hollick, Ann L. (Book collections on Project MUSE., 2017)
The law of the sea, one of the oldest and most highly developed areas of international law, has changed significantly in the past fifty years in response to rapid scientific and technological advances coupled with an increased population and the need for additional resources. Ann Hollick documents these changes and examines the evolution of U.S. ocean policy in the larger contexts of American foreign policy and of international law and politics. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.